EXPLORING COMMUNICATIVE LANGUAGE TEACHING AS AN EFFECTIVE METHODOLOGY IN ENGLISH LANGUAGE EDUCATION - Aliqulova , Mohinur; Xasanova, Feruza; Azimjonovna, Zaynab (Educational Research in Universal Sciences, 2023)
This article delves into the theme of Communicative Language Teaching (CLT) and its efficacy as a methodology in English Language Education. Beginning with a historical overview, it traces the evolution of language teaching from traditional methods to the emergence of CLT. The article explores key principles such as prioritizing communication as the primary goal, integrating real-life scenarios, adopting a student-centered approach, and promoting interactive learning. Strategies and techniques employed in CLT, including the use of authentic materials, task-based activities, and collaborative work, are examined in detail. The article discusses the advantages of CLT, emphasizing the development of practical language skills, increased motivation, cultural awareness, and enhanced intercultural competence. It also addresses challenges and criticisms associated with CLT, such as assessment difficulties and adapting to diverse learning environments. The inclusion of case studies and success stories highlights the positive outcomes of implementing CLT. Looking to the future, the article explores trends, innovations, and the role of technology in shaping the landscape of language education. Overall, it advocates for the continued exploration and integration of CLT in English Language Education to meet the evolving needs of learners in our globalized world.